Faktor-Faktor Yang Mempengaruhi Perilaku Pemeliharaan Kebersihan Gigi Dan Mulut Ibu Hamil Di Puskesmas Kabupaten Kupang - APPLONIA LEU OBI (JURNAL INFO KESEHATAN, 2017)
During pregnancy, the mother's oral cavity is susceptible to inflammation due to hormonal changes, causing the gingiva to become sensitive when oral health is not maintained. This study aims to determine the factors - factors that influence the hygiene and oral hygiene care behavior of pregnant women in Puskesmas Kabupaten Kupang. The analytic observational study with a cross-sectional design is done by taking the subjects of 97 pregnant women. Measuring tool of this study using questionnaires prepared by a Likert method is to measure the variable attitude, facilities, and infrastructure of dental health services and hygiene and oral hygiene care behavior of pregnant women. Questionnaires with two choices (true or false) to measure the known variables and services of the public health center officers and multiple choice questionnaires to measure the host habit variable. The questionnaire has been tested for validity (correlation value ≥ 0.30) and reliability with Cronbach ɑlpha> 0.60. To measure the level of education and socioeconomic status by filling in the field. Inspection of dental and oral hygiene status is done to find out the hygiene and dental hygiene maintenance behavior of pregnant women. Analysis of data by using analysis: correlation and multiple regression at a significance level <0.05. The result of multiple regression analysis showed that the level of education, facilities and infrastructure of dental health services did not significantly affect the behavior of α <0,05. The variables of socioeconomic status, knowledge, attitude, customs, dental and mouth hygiene status, service of puskesmas officers significantly correlated with dental and oral hygiene (F = 21,206, p = 0,000 *)) contributed 53,8%. Knowledge gives the biggest influence that is 20,0% to behavior of dental and oral hygiene. Conclusion: 1). The better the socioeconomic status, knowledge, attitude, dental and oral hygiene status, puskesmas service staff and the better the care of oral hygiene and mouth and the more often the habit of getting worse dental and oral hygiene maintenance behavior. 2). The level of education, facilities and infrastructure of dental health services do not give a significant effect on the maintenance behavior of oral hygiene.